Predictive‐based optimal automatic formation control of mobile vehicles. Issue 4 (12th November 2021) - Zanma, Tadanao; Haga, Shunta; Koiwa, Kenta; Liu, Kang‐Zhi
Abstract: In recent years, formation control has received a great deal of attention as one of the most interesting issues in multiple mobile robots systems. In variable formation control systems, multiple mobile vehicles can form an appropriate formation from a list of possible formations, such that all mobile vehicles can pass even when the width of the course is narrow, and simultaneously the vehicles maintain a set distance between the course and each vehicle. This paper presents a predictive‐based automatic formation control. In our formation control system, a unique formation is determined from feasible formations at any given sampling point. This control is formulated by its corresponding mixed‐integer quadratic programing by introducing binary variables that are used to specify the formation. The effectiveness of the proposed methods is verified by applying two‐wheeled mobile vehicles through simulations and experiments.